Inpatient Suicide Second Victim Experience and Support Tool: Psychometric properties of a scale for nurses who experienced inpatient suicide at Chinese general hospitals. (13th October 2020) - Tan, Rong; Luo, Kaiyan; Hu, Deying; Zhao, Yue; Han, Yanhong; Xu, Ke
Abstract: This study describes a psychometric scale, the Inpatient Suicide Second Victim Experience and Support Tool, for evaluating physical and psychological distress with a focus on resources for supporting the needs of nursing professionals. Our study defines "second victim" as a nurse who experiences inpatient suicide while on shift. We conducted a cross‐sectional study among non‐psychiatric nurses to examine the psychometrics of the scale. A total of 731 participants were recruited from eight Chinese general hospitals for this research. Data were analyzed by exploratory factor analysis and confirmatory factor analysis to examine the reliability and validity of the scale. The results indicated adequate indices resulting in 21 items. The final structure for the scale was categorized into five domains: psychosomatic distress, support from family and friends, work‐related support, organizational support, and professional self‐efficacy. The total variance explained was 69.06%. Cronbach' s alpha was 0.869 overall, and ranged from 0.626 to 0.914 for the five dimensions. The test–retest reliability of 0.792 for the entire scale was also acceptable. The scale shows promise for use by healthcare organizations to identify second victims and promote necessary organizational support interventions in Chinese hospitals.